2003
DOI: 10.1002/rcm.1078
|View full text |Cite
|
Sign up to set email alerts
|

An efficient chemical method for dephosphorylation of phosphopeptides

Abstract: Phosphate moieties found on serine, threonine or tyrosine residues in peptides, e.g., in proteolytic digests of proteins, were cleaved using hydrofluoric acid or hydrogen fluoride-pyridine without side reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…These results indicated that the stimulation might be caused by the binding of the BAF in SC to ⌬TM, which is known to mediate the binding of emerin to chromatin, because (i) the stimulation of the binding was not suppressed by kinase inhibitors, (ii) the stimula- (upper, 11-13, 17-25). Slashed boxes indicate the hydrophobic amino acid-rich region, which was demonstrated by Wolff et al (31). Two GST-fused emerin fragments were constructed and used in this study (middle and lower).…”
Section: Resultsmentioning
confidence: 90%
“…These results indicated that the stimulation might be caused by the binding of the BAF in SC to ⌬TM, which is known to mediate the binding of emerin to chromatin, because (i) the stimulation of the binding was not suppressed by kinase inhibitors, (ii) the stimula- (upper, 11-13, 17-25). Slashed boxes indicate the hydrophobic amino acid-rich region, which was demonstrated by Wolff et al (31). Two GST-fused emerin fragments were constructed and used in this study (middle and lower).…”
Section: Resultsmentioning
confidence: 90%
“…The chemical dephosphorylation of patatin was performed with hydrogen fluoride-pyridine (HF-P) as previously described [28,29], with some modification [10]. An amount of 1 mg of total protein extract from tuber of cv.…”
Section: Chemical Dephosphorylation Of Patatinmentioning
confidence: 99%
“…Second, direct and rapid in-gel multiplex identification and mapping of phosphorylated isoforms of the patatin were achieved using the Pro-Q Diamond phosphoprotein stain (Pro-Q DPS), which specifically binds to the phosphate moieties of phosphoproteins [27]. Third, quantitative profiling of phosphorylated patatin isoforms was assessed by chemical dephosphorylation of phosphoproteins with hydrogen fluoride-pyridine (HF-P) [28][29][30]. For this purpose, the volume difference between phosphorylated and dephosphorylated 2-DE patatin spots was used to quantify protein phosphorylation levels.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving this relies on complete de phosphorylation of proteins in a sample by hydrogen fluoride treatment. Chemical de phosphorylation by hydrogen fluoride has been shown to non-specifically remove post-translational modifications from proteins without affecting its integrity [23]. To determine in vivo phosphorylation status of a specific protein using RIKA, the protein is purified from the cell lysate using a specific tag or antibody raised against that protein.…”
Section: Reverse In-gel Kinase Assay (Rika)mentioning
confidence: 99%